On direct methods for solution of regularized equations - Pereverzev, S. V.; Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove that the application of so-called adaptive direct methods to approximation of Fredholm equations of the first kind leads to a more economical way of finite-dimensional approximation as compared with traditional approaches.